The role of hand dominance and sensorimotor congruence in voluntary movement - Serrien, Deborah J.; Spapé, Michiel M. (Springer, 2009)
The present study evaluated the neural changes due to effector use (unimanual left, unimanual right, bimanual) and visuomotor conflict induced by mirror-reversed vision during drawing behaviour. EEG phase synchronization, expressing interregional communication, showed that visuomotor incongruence perturbed information processing in both hemispheres. Furthermore, it was observed that the left hemisphere became temporally dominant when movements were executed with visuomotor conflict, independent of the performing hand(s). This observation emphasizes the superiority of the left hemisphere to control complex movements. In addition, the functional interactions between the hemispheres were also perturbed due to visuomotor discordance, indicating the crucial role of interhemispheric communication for movement control. These results highlight that functional connectivity patterns provide higher-order coding mechanisms of information processing. The data further underline the significance of the left hemisphere for intricate visuomotor skills.